Study Seismotectonic Around Kalimantan Island Using Likelihood Method - Haryanto, Iyan; Lamba, Lisa; Ayu, Shinta; Sunardi, Edy (Faculty of Geological Engineering, Universitas Padjadjaran, 2021)
Based on Indonesia Seismicity Map and Indonesia Seismotectonic Unit Map (Geological Research and Development Center, 2003), it can be seen that the Kalimantan Island area has the lowest earthquake vulnerability compared to other regions in Indonesia. However, in past recent years, there have been several destructive earthquakes occur in this area. As it occurred on June 5, 2015, in Ranau area with a magnitude of 6, on December 21, 2015, in Tarakan area with a magnitude of 6.1, on June 24, 2016, with a magnitude of 5.1, on 25 February 2015 with a magnitude of 5.7 in the northeast of Tarakan and 12 July 2018 in Katingan with a magnitude of 4.2. This indicates that the possibility of a potential earthquake in the Kalimantan area can still occur. For this reason, it is necessary to identify seismotectonics and the recurrence period to ensure the potential for earthquake hazards on the Island of Kalimantan. The likelihood method is used to calculate those parameters with earthquake data from 2009-2020 with a magnitude ≥ 5 and a depth of 0 – 350 Km sourced from the Meteorology, Climatology and Geophysics Agency (BMKG). Based on the calculation results, it is obtained that the value of a is 2.71222 and the value of b is 0.64077. In general, it can be concluded that the seismicity level of Kalimantan Island is quite low.Keyword: Seismotectonic, Kalimantan Island, Seismicity index, likelihood method